Oblicz :

a) √(4-2√3∙) √(4+2√3=)

b) ∛(16-2√10) ∙∛(16+2√10) =

c) √((2√7-√5)∙(2√7+√5) )=

d) (√(6&32)/(2√2-2))^3-[(6+5√2)/(2√2-2)-1/2 (2+√2)^2 ]=

http://www8.speedyshare.com/data/350175931/19387254/43628385/yyyytt.JPG

2

Odpowiedzi

Najlepsza Odpowiedź!
2009-11-20T17:01:22+01:00
A) √(4-2√3∙) √(4+2√3=)=√(4-2√3)*(4+2√3)=√4²-2√3²=√16-12=√4=2

b) ∛(16-2√10) ∙∛(16+2√10) =³√16²-2√10²=√256-40=√216

c) √((2√7-√5)∙(2√7+√5) )=√2√7²-√5²=√28-25=√3

d) (√(6&32)/(2√2-2))^3-[(6+5√2)/(2√2-2)-1/2 (2+√2)^2 ]=
nie wiem co jest w pierwszym nawiasie....
2009-11-20T17:41:58+01:00
Rozwiązania w załączniku. Ps. nie jestem pewna co do przykładu d